2009
DOI: 10.1103/physrevb.79.235336
|View full text |Cite
|
Sign up to set email alerts
|

Real-time simulations of nonequilibrium transport in the single-impurity Anderson model

Abstract: One of the main open problems in the field of transport in strongly interacting nanostructures is the understanding of currents beyond the linear response regime. In this work, we consider the single-impurity Anderson model and use the adaptive time-dependent density matrix renormalization group (tDMRG) method to compute real-time currents out of equilibrium. We first focus on the particle-hole symmetric point where Kondo correlations are the strongest and then extend the study of the nonequilibrium transport … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
242
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(253 citation statements)
references
References 54 publications
11
242
0
Order By: Relevance
“…In earlier work 31 we have found that the 2B approximation is in excellent agreement with accurate TD-DMRG results in the regime of weak to intermediate interaction strength for the Anderson impurity model. 35 Hence the 2B approximation is extremely useful for benchmarking other approximations. The main quantity of MBPT is the Keldysh Green's function, G(z,z ), where z and z are time coordinates on the Keldysh contour C. [47][48][49] To describe the electron dynamics of the system, the Keldysh Green's function is propagated in time according to the KB equations.…”
Section: Many-body Technique: Kadanoff-baym Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work 31 we have found that the 2B approximation is in excellent agreement with accurate TD-DMRG results in the regime of weak to intermediate interaction strength for the Anderson impurity model. 35 Hence the 2B approximation is extremely useful for benchmarking other approximations. The main quantity of MBPT is the Keldysh Green's function, G(z,z ), where z and z are time coordinates on the Keldysh contour C. [47][48][49] To describe the electron dynamics of the system, the Keldysh Green's function is propagated in time according to the KB equations.…”
Section: Many-body Technique: Kadanoff-baym Equationsmentioning
confidence: 99%
“…The calculations are performed with the fully self-consistent second-Born (2B) and GW approximations which have recently been shown 31 to agree with numerically exact TD-DMRG results. 35 In all cases studied here where adiabatic DFT and HF theory predict bistability dynamical XC effects destroy the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…79 Other efforts along the same direction include the numerical path integral approach, [80][81][82] real-time quantum Monte Carlo simulations, 83,84 the numerical renormalization group approach, 85 and the time-dependent density matrix renormalization group approach. 86 For a comparison and an overview of various different methods in the related problem of nonequilibrium transport with electron-electron interaction, see Ref. 87.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these studies are restricted to the steady-state regime, more recently there has been increasing activity to describe the time evolution towards the steady state as the system is driven out of equilibrium by applying a bias in the leads. These studies use a range of methods such as, e.g., TDDFT [2,[17][18][19][20], generalized master equations [21], many-body perturbation theory [22][23][24], the timedependent density-matrix renormalization group [25][26][27], a quantum trajectory approach [28], or real-time path integral [29] and Monte Carlo approaches [30].…”
Section: Model Hamiltonian For Time-dependent Transportmentioning
confidence: 99%